Analysis of YouTube Videos as Educational Media Using the Naive Bayes Method - Phung, Mulan; Anggreiny, Phoebe Cecilia; Husada, Yusianne Kasih; Pangandaheng, Grasella Aldonia; Arwi, Adelia Vannissa; Mawardi, Viny Christanti (APTIKOM SUMSEL, 2024)
Social media has become a way for people to socialize without meeting face to face, seek knowledge, sell, and so on. Analysis of the video “How Old is the Universe? (And How Do You Know?